2017
DOI: 10.21614/chirurgia.112.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Early Spontaneous Graft Intra- and Perihepatic Hematoma after Liver Transplantation

Abstract: RezumatHematomul grefei este o complicaţie cu risc vital în transplantul hepatic şi nu există în literatură concluzii clare în privinţa tratamentului acestuia, cu excepţia celor din rarele prezentări de caz publicate. Hematomul grefei poate fi intrahepatic sau subcapsular, şi se poate dezvolta spontan sau ca urmare a unor injurii hepatice ori a unor manevre invazive transhepatice percutane. Prezentăm cazul unui pacient de 62 de ani care a beneficiat de un transplant hepatic ortotopic cu ficat întreg pentru hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was found ( 30 ) that among patients with locally advanced diseases without distant metastases, those who underwent palliative gastrectomy had a higher short-term survival rate. Relevant data of palliative total gastrectomy (PTG) for stage IV proximal gastric carcinomas suggested that compared with no operation, laparotomy and jejunostomy, the PTG of stage IV proximal gastric carcinomas better prolongs the survival time and improves the quality of life ( 31 , 32 ). However, despite the feasibility and safety of PTG, it is necessary to select appropriate patients with stage IV proximal gastric carcinomas for this therapy and thoughtful preparations should be made during the perioperative period ( 33 ).…”
Section: Palliative Gastrectomymentioning
confidence: 99%
“…It was found ( 30 ) that among patients with locally advanced diseases without distant metastases, those who underwent palliative gastrectomy had a higher short-term survival rate. Relevant data of palliative total gastrectomy (PTG) for stage IV proximal gastric carcinomas suggested that compared with no operation, laparotomy and jejunostomy, the PTG of stage IV proximal gastric carcinomas better prolongs the survival time and improves the quality of life ( 31 , 32 ). However, despite the feasibility and safety of PTG, it is necessary to select appropriate patients with stage IV proximal gastric carcinomas for this therapy and thoughtful preparations should be made during the perioperative period ( 33 ).…”
Section: Palliative Gastrectomymentioning
confidence: 99%